Stellar Populations and the Star Formation Histories of LSB Galaxies—Part I: Optical and Hα Imaging - James Schombert; Tamela Maciel; Stacy McGaugh (Advances in Astronomy)
This paper presents optical and Hα imaging for a large sample of LSB galaxies selected from the PSS-II catalogs (Schombert et al., 1992). As noted in previous work, LSB galaxies span a range of luminosities (−10>𝑀𝑉>−20) and sizes (0.3kpc<𝑅𝑉25<10kpc), although they are consistent in their irregular morphology. Their Hα luminosities (L(Hα)) range from 1036 to 1041 ergs s−1 (corresponding to a range in star formation, using canonical prescriptions, from 10−5 to 1 𝑀⨀ yr−1). Although their optical colors are at the extreme blue edge for galaxies, they are similar to the colors of dwarf galaxies (Van Zee, 2001) and gas-rich irregulars (Hunter and Elmegreen, 2006). However, their star formation rates per unit stellar mass are a factor of ten less than other galaxies of the same baryonic mass, indicating that they are not simply quiescent versions of more active star-forming galaxies. This paper presents the data, reduction techniques, and new philosophy of data storage and presentation. Later papers in this series will explore the stellar population and star formation history of LSB galaxies using this dataset.